Screening Woolf : Virginia Woolf on/and/in film - Ingersoll, Earl G., 1938- (Fairleigh Dickinson University Press, 2016)
Screening Woolf: Virginia Woolf and/on/in Film examines the three film adaptations of her novels To the Lighthouse, Orlando, Mrs. Dalloway; her theorizing about film and its impact on her thinking about fiction; and her central role in the David Hare/Stephen Daldry adaptation of Michael Cunningham's Pulitzer Prize-winning novel The Hours, a role that earned Nicole Kidman an Oscar and the scorn of many Woolfians.